2002
DOI: 10.1177/0743558402175001
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Parental Separation Anxiety on Identity Development in Late Adolescence and Early Adulthood

Abstract: A longitudinal study of first-year college students and seniors was conducted in order to investigate the relationships between parental separation anxiety and adolescent identity development. Data was collected from mothers, fathers, and adolescents in the autumn and again in the spring. Mothers and fathers completed the parental separation anxiety questionnaire with two subscales, Comfort with Secure Base Role, and Anxiety about Adolescent Distancing. Their adolescent children completed the Revised Extended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 20 publications
(21 reference statements)
1
37
1
2
Order By: Relevance
“…Previous research has indicated that parental separation anxiety has negative implications for the child's development towards more independent and mature-like functioning (Bartle-Haring et al, 2002;Hock et al, 2001;Kins et al, 2011) and for the child's general well-being (Soenens et al, 2006). As a result, high levels of separation anxiety in parent-child relationships may warrant therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has indicated that parental separation anxiety has negative implications for the child's development towards more independent and mature-like functioning (Bartle-Haring et al, 2002;Hock et al, 2001;Kins et al, 2011) and for the child's general well-being (Soenens et al, 2006). As a result, high levels of separation anxiety in parent-child relationships may warrant therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Separation-related concerns are likely to surface again when a child reaches the phase of adolescence and emerging adulthood and makes the transition from a dependent adolescent to an independent young adult. For instance, the process of leaving the parental home during emerging adulthood is a real-life separation experience that might be experienced as challenging (Bartle-Haring, Brucker, & Hock, 2002;Mayseless, Danieli, & Sharabany, 1996). It has been expected and found that the way how people cope with such separation experiences depends on their attachment representations (Bernier, Larose, & Whipple, 2005;Mayseless, et al, 1996).…”
mentioning
confidence: 99%
“…In fact, a controlling family environment may be an adaptation among families caring for a child with chronic illness due to the considerable physical, psychological, and social demands placed on families related to medical management (21). In the context of JFM, the utilization of control to maintain the family system may be motivated by parents’ excessive concern for their child’s well-being and a degree of protective parenting behavior, which might stem from an underlying component of parental anxiety (11, 22). Thus, a controlling family environment may be adaptive in the short term because it helps parents manage anxiety about their child’s health and regulate their own exposure to stress by maintaining predictability in the family system, but it may be maladaptive for teens in the long run as it unintentionally hinders development of the adolescents’ independence in illness self-management.…”
Section: Discussionmentioning
confidence: 99%
“…It also has been found that being in a romantic relationship is associated with a heightened sense of self-awareness (Crouter & Booth, 2006). While relationships with parents have been found to be important to emerging adults (Bartle-Haring, Brucker, & Hock, 2002), emerging adults are focused on recentering the parent-child relationship (e.g., Tanner & Arnett, 2011). Research suggests that this does become a reality for many as emerging adults typically report increased positive relationships with their parents during this time, including an increase in open communication as well as higher levels of appreciation and respect (Lefkowitz, 2005).…”
Section: Relationship Qualitiesmentioning
confidence: 99%